An Introduction to the Masterbuilders of Traditional Architecture - Bahram Ghadiri (صفه)
n the last issue of "Sorrell", with the intention of recognizing the important role pla∎ed by the traditional master-builders in producing valuable masterpieces we introduced "Ostad Hadji ,Ali-Akhar Akhond", a traditional Architect from the city of Yazd. In this issue we intend to present another great master-builder of this land, "Ostad Mohammad-Reza Memaran Benam",Known as "Ostad RCM" Although this Ostad is from Tabriz, he is a well krown to all Iranian artists.This article is the result of an interview which took place at the Ostad's home in Tabriz on the 18 th. of Rahman, 1372.Unfortunately at the time the Ostad was suffering from heart disease and Bronchitis therefore the interview had to he shortened.It is sad to see that except for a single interview arranged by Radio and Television no suitable measures have been taken to preserve the knowledge and experiences of this great Ostad of traditional persian architecture. It is up to the administrators of the Cultural heritage Organizations and also the schools of Architecture to make an effort to preserve the experiences of the great master-builders of our time who are our only link to the true meaning of "Mimar".Here I would like to thank the cultural Heritage office in Tabriz for helping us in every way. A video film of this interview is available at the archives of the faculty of Architecture, Shaheed lleheshti University.According to his identification papers Ostad "Mohammad-Reza Ostadan Benam" was born On the first of Mehr, 1282; although he himself claims to be 85 years. old. He was born at No.5515 in the Ghareh-Aghaj, Darband and rajvieh area of Tabriz. his father was Ball.-Kazem one of the skilled builders of Tabriz. He has three wives, ten sons and six daughters.Ostad Reza became interested in Architecture at the age of twenty and Learned Architecture from his father who lived to be 115. According to Ostad Reza he has worked as a master-builder for 105 .sears and has done a wide variety of work from tine detailing to building structures. We asked him how he became interested in Architecture and building and this was his reply:"My father took me to the 'Jame' mosque to his brother Haj Sheikh Hossein who was the prayer leader to study religious sciences. After studying for a short while I realized that to gain a high position in this field one must acquire a lot of knowledge but on the other hand while dealing with religious matters there are many different views and opienions to take into consideration. Therefore I realized that it would not be possible for me to obtain perfection in this field. So I turned to science and crafts then started to work by studying the qualities of water, air, earth and fire. After that I decided to follow in my father's footsteps. This decision brought me great fame.The Ostad's first job assisting his father was the restoration of a bridge in the "Salamat-abad" village in Bijar that he turned to building public baths. He built two in Shabestar. He also built many public baths in other towns of Azarbaijan including Meshkin-shahr, Mamaghan, Litvan, etc. Ostad Reza says that because of winning great fame in building baths people came to him from all different areas of Tabriz asking him to build for them.After this he was asked to restore the "Kabood mosque" in tabriz. He says: I started work on the "Kabood mosque" by studying the qualities of different materials. I noticed that stones were being placed in plaster. I told the builders that the stones had not been backed by fire therefore they absorb a lot of water. The stones used should come from a plaster-kiln. I suggested they build a mill and also a plaster-kiln. This way I got hold of stones that would absorb less water and with them I built a dome for the mosque that will stand for thousands of years. The Ostad considers this dome as the best work he's ever done.He says : "An architect is never free while designing a building for the agreement of the employers is always a very important factor but in the "Kabood mosque" I used strong bricks therefore if not ruined by an earthquake it will stand for thousands of years."Ostad Reza has done a lot of work from building, restoration and design to supervising different projects. His speciality is building pubilc baths. Here we have a list of the Ostad's work. This list though incomplete may be considered a first step towards recording all the work ever done by this great master-builder.We asked the Ostad how many builders and architects lie had trained. lie answered : "Being an apprentice requires a lot of patience and natural talent My apprentices couldn't endure the hard work and usually left me. "After this lie remembered a story which he told us : "Once when I was twenty years old, While accompanying my father and a group of learned men in the presence of "Sheikh-Ol Aemmeh" who was the judge, the Sheikh asked my father : Which of your children shall serve the people like you? "My father pointed at me with his broken walking stick and said: "Haj Sheikh, my son Reza. I shall have to serve him as an apprentice for 30 years. "At the time my father was a great Ostad and I had not yet begun studying Architecture therefor I was surprised at what my father said. Later on I realized that lie had seen inside me something I was not yet aware of myself.Of the Ostad's children only two of his sons followed their father's steps. When we asked why, he replied: "When I became well-known and wealthy in Azarbaijan about 51 years ago I bought this house. Next to it was a vacant plot of land, and a lot of unsuitable people gathered, there. This was an unfit environment for my children's upbringing and had a negative effect on them.The Ostad believes that becoming an "Ostad" in every way needs a lot of time and an architect must know the four elements (water, air, earth, fire) very well. Not being familiar with the four elements is harmful to the building and makes it unsuitable for people.We asked Ostad-Reza what lie thought was the most important thing for a student of Architecture today. He answered: "Obtaining experience. Students should practice. "We asked him about the Architecture of today. He said: "Building materials have changed. This building I'm living in is made of mud-bricks but they are not used anymore. Work done with mud-bricks is much different from work done with cement. By changing building materials we have weakened our knowledge. Today if there is no cement and iron a builder cannot work. I built the 19.8 meter diameter dome of the "Kabood mosque" with old materials because the building is very old. The dome is very strong. But in the building of the "Imam Reza (greeting on him) Mosque" outside Tabriz I used concrete because this building belong to this era and I believe it will' stand for thousands of years.The above named mosque is the Ostad's last work. Work on the mosque's roofs, dome and minerets will be carried out soon.List of works done by Ostad-Reza :Built by Ostad Reza1) 50 public baths including- Mafi-0- dolleh bath in Meshkin Shahr,- Dah- Navardi public bath,- Mamaghan public bath- Litvan, Harris, Deh- Barnlo public bath...2-   A stone dam built outside Takab. The bottom of the dam is 18 meters thick and the top is 10 meters thick. This dam is 100 meters long.3-   Dr. Kazem-Zadeh's prirvate house in Tabriz.4-   The dome of the mosque in the Sanatti Sharif University campus, Tehran.5-   The "Imam Reza (greeting on him) mosque" outside Tabriz.Restored by Ostad Reza:1-  The Salamat-Abad bridge in Bijar.2-  Restoring over 300 public baths including "Sanjagh" "Seffead" and "Nokhost" public baths, the "Khan" public bath near Tabriz bazaar that was originally built in the Safavied period and has unfortunately been destroyed and replaced by the "Safavid Timcheh".3-The "Kabood mosque".4-  The dome of the "Kabood mosque.5-  The "Kolandooz chaharsoogh" in the Tabriz bazar6-  Restoring many parts of Tabriz bazar.7-  The "Ayatollah Shahidi mosque" next to the "Kabood mosque".8-  Repairing the "Bani Akram mosque" in Tabriz.Supervised by Ostad Reza :1-  Rebuilding "Taviseh" of, the "Alchagh mosque" in Tabriz.2-  Repairing the "Safli Bazar" in Tabriz.3-  Building the Agricultural buildings in Ardebil, Mamaghan, Pars-Abad.Connecting the roof of the "Khaleh Oofi mosque" to the "AlChagh mosque" rear" jame mosque", Tabriz.